Hilda must be dancing - Wilson, Karma; Watts, Suzanne (New York : Alladin Papervbacks/Simon and Schuster, 2004)
None of her jungle friends can find Hilda Hippo a quieter, less disruptive replacement for dancing, her favorite hobby, until Water Buffalo suggests an activity that allows Hilda to express her dance creativity in a new way.
Accelerated Reader AR
Keywords: Hippopotamus -- Fiction; Dance -- Fiction; Jungle animals -- Fiction; Stories in rhyme